Ether in Kant and akasa in Prasastapada: Philosophy in comparative perspective - Tola, Fernando; Dragonetti, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The study of Indian and Western systems of Philosophy reveals many points of thematic and methodological coincidences between them. We have collected a good number of these coincidences in our recent books, where we have included many philosophical texts in Sanskrit and in European languages which contain the expression of astonishing similar ideas and theses. In the present article we add a new instance of coincidence between Indian and Western thought in relation to akasa in India (limited to the Indian philosophical system Vaisesika) and ether (Aether or Äther in German) in the Opus postumum of Kant. The inexistence of both akasa and ether has been established by Modern Science. Akasa and ether in India and the West, respectively, constitute a notorious example of asrayasiddha, the well-known logical defect considered by Indian Logic.
Keywords: ether; Kant; akasa; Prasastapada; Opus Postumum; Vaisesika; Philosophy